Adopsi Blockchain pada Praktik Akuntansi di Indonesia: Systematic Literature Review - Habi Bullah; Rian Abrori (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
This article aims to analyze the potential of blockchain adoption for accounting in Indonesia. This study uses the SLR model or Systematic Literature Review. The result find blockchain adoption in accounting practices is a crucial strategy to enhance the quality, transparency, and efficiency of accounting systems. This technology holds significant potential for application across various sectors, including transaction recording, auditing, financial reporting, taxation, Islamic finance, and accounting education. However, the successful adoption of blockchain largely depends on the availability of adequate regulatory frameworks, technical standardization, professional training for accountant, and the integration of blockchain-related content into accounting curriculum.